A Alegoria em Matemática - Machado, Nílson José (Estudos Avançados, 1991)
The characterization of style in mathematical texts and the similarity of functions performed by metaphors, allegories and models as links between distinct semantic fields are the start point in examining the presence of allegoric constructions in mathematical teaching. Several examples are analysed, suggesting the essentiality of making use of such constructions and concluding that the permanent transition between the literal and the figurative senses is the motor of creative processes in Science and Mathematics, as in Language.